Safety assessment of L-Arg oral intake in healthy subjects: a systematic review of randomized control trials - Kuramochi, Yui; Murata, Mai; Sumino, Akihide; Sone, Hideko; Hayamizu, Kohsuke (Amino acids, 2023)
L-Arg is a nonessential amino acid but has many physiological roles. Accordingly, L-Arg has been used in various fields, but there is only limited information available about its safety upon overdose. Generally, the no-observed adverse effect level (NOAEL) is used when setting the upper amount for chemical substances. Recently, systematic reviews have been used to assess the safety as well as the effectiveness and usefulness of them. Therefore, we conducted an assessment of the safety of the oral intake of L-Arg in healthy subjects using gastrointestinal symptoms as an index. We limited the study design to only double-blind randomized controlled trials and searched PubMed, Cochrane Library, EBSCOhost, and Ichushi-Web from inception until May 2021. Assessment of the quality of studies was conducted using the Cochrane Collaboration tool and Jadad score, and the random effects model was used for data analysis. Ultimately, 34 studies were selected for inclusion in this work. The dosage of L-Arg used in the studies ranged from 2000 to 30,000 mg/day (or/one-time dose), and the treatment duration was 1–84 days. The increased risk of gastrointestinal symptoms associated with L-Arg intake from 23 studies (647 participants in total) in which such symptoms were reported was 0.01 (95% confidence interval: – 0.02–0.04), which was not significant difference. NOAEL was estimated as 7531 mg/ one-time dose using a weighted change-point regression model (UMIN000046133). Registration and protocol : Umin.ac.jp as UMIN000046133.